Reactivation and foetal infection in pregnant heifers infected with neospora caninum live tachyzoites at prepubertal age - Hecker, Yanina; Burucúa, Mercedes María; Fiorani, Franco; Maldonado Rivera, Jaime; Cirone, Karina Mariela; Dorsch, Matías; Cheuquepan Valenzuela, Felipe; Campero, Lucia Maria; Canton, German Jose; Marín, Maia; Ortega Mora, Luis; Moore, Prando Dadin (MDPI, 2022)
Neospora caninum is recognised for causing cattle abortion, provoking severe economic losses in the livestock industry worldwide. The aim of the present study was to evaluate the reactivation and foetal infection in pregnant heifers inoculated with live N. caninum tachyzoites before puberty. A total of 15 30-month-old pregnant heifers were allocated into four groups: animals inoculated with live tachyzoites of NC-Argentina LP1 isolate before puberty and challenged with live tachyzoites of NC-1 strain at 210 days of gestation (DG) (Group A); animals mock inoculated before puberty and challenged with NC-1 strain at 210 DG (Group B), animals inoculated before puberty but not subsequently challenged (Group C); and noninfected and nonchallenged animals (Group D). The results of this study showed that 100% of animals infected before puberty (Groups A and C) suffered reactivation of the infection at the seventh month of gestation. In addition, in three and two calves from Groups A and C, respectively, congenital infection was confirmed. Interestingly, we provide evidence that the use of live N. caninum tachyzoites in young animals as a strategy to induce protection is neither safe nor effective.